Perbandingan Kadar Hemoglobin dan Hematokrit Saat Menstruasi dan Sesudah Menstruasi pada Remaja Putri - Ayuk Pitaloka; Ismarwati Ismarwati; Monika Putri Sholikah (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Menstruation is a physiological process characterized by bleeding from the uterine wall in women, resulting in blood loss that lowers hemoglobin and hematocrit levels, which can lead to anemia. Anemia among adolescents can affect concentration, physical endurance, and academic performance. This study aimed to analyze the comparison of hemoglobin and hematocrit levels during and after menstruation. The method used was an observational analytical pre-experimental design employing a pretest-posttest one-group design. The study population consisted of 114 female students from Universitas 'Aisyiyah Yogyakarta, selected using purposive sampling with a sample size of 35 students. The instrument used was the Quick Hemoglobin Meter, employing the reflectance photometer method. Data were analyzed using the paired t-test with a significance level of p≤0.05. The analysis results showed a significant difference between hemoglobin and hematocrit levels during and after menstruation, with a significance value of 0.000 (p ≤0.05) respectively. This study concludes that there is a statistically significant difference between hemoglobin and hematocrit levels during and after menstruation in adolescent girls.